Improvisation as a place of discovery and reinvention in times of pandemic - Vieira, Marcilio de Souza (2022)
In this interview, improviser from Minas Gerais Dudude Herrman talks about improvisation, about the Decanto de Dança project and improvising for the screen. The interview was done with the artist via WhatsApp, as we are still experiencing the Covid-19 pandemic. It aimed to understand how the artist and researcher Herrmann understands improvisation and how it was used on canvas. The artist gives us valuable clues in this interview to understand her relationship with improvisation.